2018
DOI: 10.1016/j.celrep.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12R-Dependent Translocation Mechanisms Gate the Changing Microglial Landscape

Abstract: SUMMARY Microglia are an exquisitely tiled and self-contained population in the CNS that do not receive contributions from circulating monocytes in the periphery. While microglia are long-lived cells, the extent to which their cell bodies are fixed and the molecular mechanisms by which the microglial landscape is regulated have not been determined. Using chronic in vivo two-photon imaging to follow the microglial population in young adult mice, we document a daily rearrangement of the microglial landscape. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 35 publications
9
102
0
Order By: Relevance
“…Seizure‐induced activation of microglia was, expectedly, characterized by time‐dependent changes in the morphological state including increase in microglial cell number, increased soma size and reduction in number of processes/process length (Avignone et al, ; Eyo et al, ). However, we found that infiltrated monocytes after status epilepticus lacked cellular processes and were highly motile cells when compared to the relatively stationary microglial (Eyo et al, ). Interestingly, microglia and monocytes showed distinct electrophysiological properties as well.…”
Section: Discussionmentioning
confidence: 99%
“…Seizure‐induced activation of microglia was, expectedly, characterized by time‐dependent changes in the morphological state including increase in microglial cell number, increased soma size and reduction in number of processes/process length (Avignone et al, ; Eyo et al, ). However, we found that infiltrated monocytes after status epilepticus lacked cellular processes and were highly motile cells when compared to the relatively stationary microglial (Eyo et al, ). Interestingly, microglia and monocytes showed distinct electrophysiological properties as well.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that microglia could proliferate multiple times during the first 3 d. Alternatively, it is also possible that microgliosis could be due to migration of SDH microglia from neighboring spinal segments (e.g., rostral L3 and caudal L5 segments) because microglia show chemotaxis. 31,32) However, infiltration of circulating monocytes in the SDH, 12) which is reported to express Iba1, does not contribute to the PNI-induced SDH microgliosis, since recent studies using bone marrow chimeric mice subjected to mild irradiation, parabiosis mice and doubletransgenic mice (enable distinct visualization of resident microglia and circulating monocytes) demonstrated no evidence for the involvement of circulating monocytes. 4,10,11) Numerous microglia induced by PNI gradually returned to pre-PNI levels, the time-course of which is similar to a recovery of PNI-induced pain hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…A gradient or threshold of these factors may start intracellular cascades in microglia that trigger division and migration, such as NF-KB signaling which has been shown to be important for microglia to repopulate fully . In addition, we show that the P2Y12 receptor is not critical to doublet formation, repopulation, or the acquisition of microglial territories (as reflected by changes in nearest neighbor quantification) in the visual cortex (Figure 2 and 3), which is surprising given that P2Y12 modulates microglial translocation in baseline conditions (Eyo et al, 2018). The progressive distribution of microglia to achieve tiling during repopulation is most likely maintained by lateral inhibition mechanisms and homeostatic microglia-specific genes such as Sal1 and Mafb-which both maintain microglia in a ramified nonclustered state (Buttgereit et al, 2016; Matcovitch-Natan et al, 2016).…”
Section: Intrinsic and Extrinsic Mechanisms Of Microglia Repopulationmentioning
confidence: 77%
“…In both the rodent and human brain, microglial numbers are maintained throughout adult life (Fuger et al, 2017;Hashimoto et al, 2013;Reu et al, 2017), with no further contribution of peripheral cells to the microglial population in the absence of pathological changes (Ajami et al, 2007;Askew et al, 2017;Bruttger et al, 2015;Elmore et al, 2015;Mildner et al, 2007). Microglia are uniformly distributed in a distinct cellular grid throughout the brain parenchyma (Eyo et al, 2018;Hefendehl et al, 2014;Nimmerjahn et al, 2005) and maintain their territories with slow translocation on a timescale of days (Eyo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%